Protein source and nutrient density in the diets of male broilers from 8 to 21 d of age: Effects on small intestine morphology. (26th December 2014) - Wang, X.; Peebles, E. D.; Morgan, T. W.; Harkess, R. L.; Zhai, W.
Abstract : In a companion study, high amino acid (AA) or apparent metabolizable energy (AME) densities in the diets of broilers from 8 to 21 d of age were found to improve feed conversion. A total of 1, 120 male Ross × Ross 708 chicks were randomly allocated to 80 pens (8 treatments, 10 replications per treatment, 14 chicks per pen). A 2 × 2 × 2 factorial arrangement of treatments was used to investigate the interaction among the protein source (high distillers dried grains with solubles diet [hDDGS] or high meat and bone meal diet [hMBM]), AA density (moderate or high), and AME density (2, 998 or 3, 100 kcal/kg) of diets on small intestine morphology. Duodenum, jejunum, and ileum samples from 2 chicks per pen were collected and measured individually at 21 d. Jejunum sections were processed for histological analysis. Chicks fed hDDGS diets exhibited longer small intestines than did chicks fed hMBM diets. Particularly, when chicks were fed high AA density diets, jejuna were longer in groups fed hDDGS diets than groups fed hMBM diets. Dietary treatments did not affect jejunum villus height, width, area, crypt depth, villus to crypt ratio, goblet cell size, or cell density. In birds fed diets containing a moderate AA and a high AME density, jejunum muscle layers of chicks fed hDDGS diets were thicker than those fed hMBM diets. Chicks exhibited a lower feed conversion ratio (FCR) and a higher BW gain when their crypts were shorter. In conclusion, an hDDGS diet may facilitate small intestine longitudinal growth in broilers, which may subsequently improve dietary nutrient absorption. In addition, broiler chicks with shallow intestinal crypts exhibited better growth performance.